The Effect of the Use of Black and White Flashcards on Acute Pain Levels in Infants - Diler Yılmaz; Nejla Canbulat Şahiner; Zübeyde Ezgi Erçelik (Çocuk Dergisi)
Objective: Vaccination practices are one of the most painful procedures in infancy, creating anxiety and distress for both infants and their parents. This study was planned to determine the effect of black and white flashcards on the level of acute pain infants feel during vaccination applications. Materials and Methods: The sample of this prospective randomized controlled trial comprised 119 infants who were brought to the family health center for the 2nd and 3rd dose of the combined 5-vaccine and who met the inclusion criteria. The data were obtained using the information form, which included descriptive characteristics of the baby and family, and the FLACC pain assessment tool. Results: The mean pain scores of the infants (2.76 ± 2.06) in the black and white flashcard group were significantly lower than those of the control group (4.61 ± 2.00) (p < 0.01). Additionally, there was statistically no significant difference between the total durations of crying and the periods of the infants between initial crying and calming down in both the experimental and control groups (p>0.05). Conclusion: We concluded that the use of black and white flashcards during the vaccination practices was efficient. In line with these results, we recommend that nurses use black and white flashcards, an easily applicable method, to decrease the pain sensitivity of infants during vaccine applications.